Zones of participation – a framework to analyse design roles in early childhood education and care (ECEC). Issue 2 (3rd April 2022) - Brinck, Jaana; Leinonen, Teemu; Lipponen, Lasse; Kallio-Tavin, Mira
ABSTRACT: Current research has addressed children's involvement in codesign from several different perspectives such as empowerment, design thinking, participation, and learning. The literature presents many roles that children can have in participatory design (PD) e.g. as testers, informants, users, co-designers, and co-researchers. Both critical views and solutions to support children's genuine participation exist. The investigation was motivated by examining whether and how children's participation can be enhanced through PD practices. The study conducted a participatory design (PD) process in a kindergarten in Finland together with adults and children. The Grounded Theory analysis elicited different roles of the participants as prominent indicators of the interaction in and quality of participatory process. These roles were further elaborated as Zones of participation (ZoP) that constituted of the Zone of audience, Zone of whisperer, Zone of actor and Zone of director. The analysis shows that there are significant co-occurrences between participant groups accessing different zones. We suggest that the quality of participation in the design process can be investigated by identifying participants' access to different ZoP. Movement between the zones indicates that there is no one-sided control over actions and dialogue between the participants is prominent.